Marketing Communications’ Message Strategies of TikTok Shop Indonesia and Shopee Indonesia Through Social Media Instagram - Rahma Maulinda Dwinari; Pawito; Andre Noevi Rahmanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
TikTok Shop and Shopee are two e-commerce sites that using Instagram as a marketing communication medium. This study aims to discover the message strategy’s from the Instagram’s contents of @TikTokShop_Indonesia and @Shopee_ID in welcoming the month of Ramadan in 2023. The message strategy theory is the reference in this study. This study uses a qualitative approach with content analysis methods. The study results show that @TikTokShop_Indonesia content focus on transformational messages, informational messages become the focus afterward, and interactional messages still need to achieve. TikTok Shop Indonesia is more focused on touching the emotional motivation of its consumers with the hope that consumer involvement will increase. Instead, @Shopee_ID puts interactional messages and transformational messages above informational messages